2020
DOI: 10.1177/1541204020939643
|View full text |Cite
|
Sign up to set email alerts
|

Is the Foster Care-Crime Relationship a Consequence of Exposure? Examining Potential Moderating Factors

Abstract: Youth who are dually involved in both foster care and criminal justice systems represent a small minority of individuals with multi-problem risk profiles. Prior research has found that foster care youth are disproportionately more likely to be chronic offenders in both adolescence and emerging adulthood. However, the nature of this relationship remains theoretically underexplored and empirically underexamined, especially with respect to risk factors that may moderate the relationship. Using data from the Incar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
3
8
0
Order By: Relevance
“…Of specific relevance to this paper, Baidawi and Sheehan (2019, p. 12) note that 'children with a "life-course persistent" offending profile may be over-represented among crossover children compared to the overall cohort of youth offenders'. This hypothesized cumulative negative association between having both child welfare and youth justice contact is in line with international evidence that a high proportion of people with convictions or experience of imprisonment in adulthood have been 'looked after' or known to social care or justice services earlier in life (Carr & McAlister, 2016;Staines, 2016;Yang et al, 2021). However, it is unclear to what extent there is a particularly unequal relationship between cross-over status and different types of adult conviction trajectories, especially persistent adult conviction trajectories, over and above the association between contact with either youth justice or child welfare in isolation.…”
Section: Literature Reviewsupporting
confidence: 65%
“…Of specific relevance to this paper, Baidawi and Sheehan (2019, p. 12) note that 'children with a "life-course persistent" offending profile may be over-represented among crossover children compared to the overall cohort of youth offenders'. This hypothesized cumulative negative association between having both child welfare and youth justice contact is in line with international evidence that a high proportion of people with convictions or experience of imprisonment in adulthood have been 'looked after' or known to social care or justice services earlier in life (Carr & McAlister, 2016;Staines, 2016;Yang et al, 2021). However, it is unclear to what extent there is a particularly unequal relationship between cross-over status and different types of adult conviction trajectories, especially persistent adult conviction trajectories, over and above the association between contact with either youth justice or child welfare in isolation.…”
Section: Literature Reviewsupporting
confidence: 65%
“…For young people in foster care, adverse educational outcomes are also more likely 13. Furthermore, a history of having been in foster care is associated with predicted higher rates of a chronic offending trajectory 14. Although these negative outcomes might not apply to all young people in foster care, they are at a higher risk than the general population 8…”
Section: Introductionmentioning
confidence: 99%
“…Given the vast literature on how offending may develop over the life course (e.g., Laub & Sampson, 2003;Matsuda et al, 2022;Moffitt, 1993), a surprisingly limited number of studies have reported how OHC experience is associated with offending trajectories. Among the few studies that do exist, all are based on crude indicators of OHC experience, small and/or high-risk samples, and where the follow-up typically does not extend beyond young adulthood (Yang et al, 2017(Yang et al, , 2021Ryan et al, 2007;Tärnhäll et al, 2023). This generally also holds for related studies on the developmental course of offending among abused and neglected individuals.…”
Section: Introductionmentioning
confidence: 99%